A randomized pilot program to reduce opioid use following dental surgery and increase safe medication return. (March 2020) - Derefinko, Karen J.; Salgado García, Francisco I.; Johnson, Karen C.; Hand, Sarah; Murphy, James G.; McDevitt-Murphy, Meghan; Suda, Katie J.; Andrasik, Frank; Bursac, Zoran; Chiu, Chi-Yang; Talley, Kevin; Brooks, Jeffrey H.
Highlights: The study examined the efficacy of opioid exposure reduction in dental patients. Intent to treat analysis indicated a non-significant trend for treatment group effect. Sensitivity analysis showed that the treated group self-reported less opioid use. A brief intervention and non-narcotic pain medication may reduce opioid use. Abstract: Research indicates that increased cumulative exposure (duration of administration and strength of dose) is associated with long-term opioid use. Because dentists represent some of the highest opioid prescribing medical professionals in the US, dental practices offer a critical site for intervention. The current study used a randomized clinical trial design to examine the efficacy of an opioid misuse prevention program (OMPP), presented as a brief intervention immediately prior to dental extraction surgery. The OMPP provided educational counseling about risks and appropriate use of opioid medication, as well as 28 tablets of ibuprofen (200 mg) and 28 tablets of acetaminophen (500 mg) for weaning off opioid medication. This was compared with a Treatment as Usual (TAU) control condition. Participants were individuals presenting for surgery who were eligible for opioid medication ( N  = 76). Follow up assessment was conducted at 1 week following surgery, with 4 individuals refusing follow up or not prescribed opioid. Intent to treat analysis indicated a non-significant treatment group effect ( N  = 72, Beta  = 0.16, p = .0835), such that the OMPP group self-reported less opioid use (in morphine milligram equivalents, MMEs) than the TAU group (37.94 vs. 47.79, effect size d  = 0.42). Sensitivity analysis, excluding individuals with complications following surgery ( n  = 6) indicated a significant treatment group effect ( N  = 66, Beta  = 0.24, p = .0259), such that the OMPP group self-reported significantly less MMEs than the TAU group (29.74 vs. 43.59, effect size d  = 0.56). Results indicate that a 10-minute intervention and provision of non-narcotic pain medications may reduce the amount of self-administered opioid medication following dental surgery.